Effects of Emotional Intelligence to Learning Achievement in Elementary School - Acoci; Suardin; Muhammad Yusnan; Saada Omar; Suhairee Berngacha (Buletin Edukasi Indonesia, 2022)
The influence of emotional intelligence on learning achievement in high-grade students of an elementary school in Wakatobi Regency, Indonesia. Emotional intelligence is one of the essential factors that should be possessed by students who need to achieve better learning achievement in school because, according to existing theories, emotional intelligence dramatically affects student learning achievement. The reality of this sat is quite interesting to study. The individual has a high chance of achieving high learning achievement. On the other hand, if a person has relatively low emotional intelligence, then that person certainly has the opportunity to get pretty low learning achievement. Whereas in reality, individuals lack emotional intelligence. High can achieve learning achievements that are biased to be proud of. This study aims to determine the effect of emotional intelligence on learning achievement in high-grade students. This study is quantitative. Variable covered emotional intelligence and learning achievement. The subjects in this study were students of the 4th, 5th, and 6th grades. The data collection method used is an emotional intelligence scale and documentation in the form of an average student report card score. The data analysis technique in this study uses simple linear regression analysis. R Square (coefficient of determination) was obtained of 0.103. This means that the effective contribution that emotional intelligence makes to learning achievement is 10.3%, while the remaining 89.6% is influenced by other factors. Such factors can be internal factors or external factors. This suggests that emotional intelligence has no effect on student learning achievement. Y=123.13+(16,555X), which means that each addition of one emotional intelligence value will reduce the learning achievement value by 16,555. These results show that emotional intelligence has no influence on learning achievement.